OPTIMIZATION OF CONTENT STRATEGY AND SOCIAL MEDIA ENGAGEMENT: A CASE STUDY OF KOPI JAGO ON INSTAGRAM - Sagala Pebri Antoni; Sumarwan Ujang; Yuliati Lilik Noor (RADJA PUBLIKA, 2024)
This study aims to analyze the content strategy and user engagement with the Instagram account of Kopi Jago, a mobile-based local coffee brand. Using content analysis, A/B testing, and sentiment analysis methods, this study evaluates 889 posts from 2019 to 2024. The results indicate that video content generates higher comments (69%) compared to photos, while shorter captions drive more likes. Neutral sentiment dominates (40%), with frequent complaints about stock availability and customer service. This research implies that a content strategy focused on video storytelling and improved customer service responses are key to building brand loyalty and a positive brand image.